2003
DOI: 10.2139/ssrn.562517
|View full text |Cite
|
Sign up to set email alerts
|

Financial Asset Returns, Direction-of-Change Forecasting and Volatility Dynamics

Abstract: W e consider three sets of phenomena that feature prominently in the financial economics literature: (1) conditional mean dependence (or lack thereof) in asset returns, (2) dependence (and hence forecastability) in asset return signs, and (3) dependence (and hence forecastability) in asset return volatilities. We show that they are very much interrelated and explore the relationships in detail. Among other things, we show that (1) volatility dependence produces sign dependence, so long as expected returns are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(58 citation statements)
references
References 78 publications
6
52
0
Order By: Relevance
“…The results in this work are also in accordance with the conclusions reached by Christoffersen and Diebold (2006). The profitability of the trading rules as well as the sign rate indicator improves substantially over the bear market period against a B&H strategy, as implied by the aforementioned paper for a higher volatility period that characterize the post‐bubble time interval in our test.…”
Section: Profitability Of Alternative Trading Strategiessupporting
confidence: 90%
See 2 more Smart Citations
“…The results in this work are also in accordance with the conclusions reached by Christoffersen and Diebold (2006). The profitability of the trading rules as well as the sign rate indicator improves substantially over the bear market period against a B&H strategy, as implied by the aforementioned paper for a higher volatility period that characterize the post‐bubble time interval in our test.…”
Section: Profitability Of Alternative Trading Strategiessupporting
confidence: 90%
“…In this study, the trading implications of conditional volatility are examined within a broader framework as concerns the nonlinear functional form of the forecast generating mechanism as well as the presence of past returns that might have forecasting power. Christoffersen and Diebold (2006) in their paper show that volatility dependence produces sign dependence and therefore forecasting ability, as long as expected returns are nonzero. The intuition behind this relationship is that volatility changes will alter the probability of observing negative or positive returns.…”
Section: Volatility Spillovers and Second‐moment Effectsmentioning
confidence: 93%
See 1 more Smart Citation
“…Empirical evidence suggests out‐of‐sample predictability of excess stock market returns based on macroeconomic variables ranges from weak to non‐predictable. Christoffersen & Diebold () and Christoffersen et al. () argued that the sign of stock returns may be predictable even when the returns are not themselves predictable.…”
Section: Dataset Examplesmentioning
confidence: 99%
“…We include the carry interest earned on the domestic or foreign currency while it is held, but ignore trading costs, which are negligible for monthly trading in the foreign exchange market. The Importance of Volatility Dynamics Christoffersen and Diebold (2006) have shown that directional predictability is inextricably linked to the dynamics of conditional volatility. In particular, they show that even if the conditional mean return is constant (i.e.…”
Section: The Day-of-the-month Effect In Momentum Trading Strategiesmentioning
confidence: 99%